APPLICATION NEURAL NETWORK IN HUMAN INTERACTION SYSTEM (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2012)
We propose a uniform work for understanding end-to-end communication security network intelligence (CSNI), which is defined as the ability of a network to act appropriately in a changing environment. We consider an appropriate action to be one that increases the optimal and efficient use of network resources in delivering services, and we define 4success as the achievement of behaviour sub-goals that support the service provider’s ultimate goals, which are defined external to the network system. The work presented incorporates the functional elements of intelligence into computational modules and interconnects the modules into networks and hierarchies that have spatial, logical, and temporal properties.